Pengaruh Faktor Motivasi Dan Disiplin Kerja terhadap Kinerja Karyawan pada Koperasi Serba Usaha (KSU) Kuta Mimba Kecamatan Kuta Kabupaten Badung - WIJAYA, I GUSTI PUTU ANGGA; SUDARMA, I MADE; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.9, No.2, Juli 2020, 2020)
Kuta Mimba KSU is aimed at people from three regions both bound by adat , dinas , and migrants. The problems that occurred regarding the performance of employees at Kuta Mimba KSU were a concern in this study. Because employee performance is very important in order to support and create cooperative progress. Factors in work discipline, motivation as a factor which is assumedto determine employee work performance at Kuta Mimba KSU. The purpose of this study was to determine the effect of motivational factors on employee performance at the Kuta Mimba Multipurpose Cooperative and to determine the effect of work discipline factors on employee performance at the Kuta Mimba Multipurpose Cooperative. This research took place at the Kuta Mimba Multipurpose Cooperative, hereinafter referred to as KSU Kuta. The population in this study was 90 employees of Kuta Mimba Multipurpose Cooperative, Kuta, Badung and the number of respondents used was 90 people using the census method. Data analysis used Mann Whitney non parametric test. Based on the results of the analysis, it is concluded that there was a significant effect between motivation and work discipline on employee performance, and U value in Mann Whitney non parametric test. There was a partial positive and significant influence between motivation on employee performance at the Kuta Mimba Multipurpose Cooperative, and there was a partial positive and significant influence between work discipline on employee performance at the Kuta Mimba Multipurpose Cooperative and there was a simultaneous positive and significant influence between motivation and work discipline on employee performance at the Kuta Mimba Multipurpose Cooperative. The management in the Kuta Mimba Multipurpose Cooperative should further improve the quality of employee motivation and discipline, because employee motivation and discipline would affect employee performance and pay attention to work discipline given to employees so that work discipline looks fair to all employees, because work discipline affects employee performance.